2008
DOI: 10.1158/1078-0432.ccr-08-1163
|View full text |Cite
|
Sign up to set email alerts
|

SCG3 Transcript in Peripheral Blood Is a Prognostic Biomarker for REST-Deficient Small Cell Lung Cancer

Abstract: Purpose: Specific markers of circulating tumor cells may be informative in managing lung cancer.Because the RE-1silencing transcription factor (REST/NRSF) is a transcriptional repressor that is inactivated in neuroendocrine lung cancer, we identified REST-regulated transcripts (CHGA, CHGB, SCG3,VGF, and PCSK1) for evaluation as biomarkers in peripheral blood. Experimental Design: Transcripts were screened across lung cancer and normal cell lines. Candidates were assessed by reverse transcription-PCR and hybrid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 45 publications
4
49
1
Order By: Relevance
“…Here, we show that cell differentiation and growth in SCLC mediated by NRSF/REST are subject to upstream regulation by methylation, which modulates downstream AKT2 signalling. The expression of neuronal genes is a phenotypic hallmark of SCLC tissue and cell lines (Coulson et al, 2000;Gurrola-Diaz et al, 2003;Neumann et al, 2004;Onganer et al, 2005;Moss et al, 2009). In this study, we determined transcripts of various neuronal marker genes in SCLC lines and correlated expression levels with those of NRSF/REST and its splice variant sNRSF, thus extending other reports on SCLC lines with reduced NRSF/REST expression.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Here, we show that cell differentiation and growth in SCLC mediated by NRSF/REST are subject to upstream regulation by methylation, which modulates downstream AKT2 signalling. The expression of neuronal genes is a phenotypic hallmark of SCLC tissue and cell lines (Coulson et al, 2000;Gurrola-Diaz et al, 2003;Neumann et al, 2004;Onganer et al, 2005;Moss et al, 2009). In this study, we determined transcripts of various neuronal marker genes in SCLC lines and correlated expression levels with those of NRSF/REST and its splice variant sNRSF, thus extending other reports on SCLC lines with reduced NRSF/REST expression.…”
Section: Discussionsupporting
confidence: 71%
“…In two SCLC lines, a complete loss of NRSF/REST transcription resulted in an increased expression of the neuronal markers, neural cell adhesion molecule (NCAM), L1-cell adhesion molecule (L1-CAM) and voltage-gated calcium channels (Neumann et al, 2004). A recent study identified the SCG3 transcript as a prognostic biomarker for NRSF/REST-deficient SCLC (Moss et al, 2009). Here, we show that NRSF/ REST-mediated cell differentiation and growth in SCLC is subject to upstream regulation by methylation, which ultimately affected the downstream AKT2 pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, elevated CHGA is an indicator for pancreas and prostate cancers. 36 Detection of SCG3 and VGF transcripts is a prognostic biomarker for small cell lung cancer and large cell neuroendocrine carcinoma, 37,38 respectively. More importantly, a putative REST response element (neuron-restrictive silencer element [NRSE]) is found in the regulatory regions such as the promoter or 5′ untranslated region (5′-UTR) of each of these genes (Suppl.…”
Section: Ews Inhibits a Subset Of Rest Target Neuronal Genes In Ewingmentioning
confidence: 99%
“…It appears conceivable that dysregulation of REST/NRSF may also play a role in aberrant L1 expression in human carcinomas. For example, REST/ NRSF has been found to be inactivated in small-cell lung cancer [106], and increased expression levels of the neuronal isoform of L1 have been found in cells of the smallcell lung carcinoma cell line NCI-H69 [107].…”
Section: Pathological L1cam Gene Regulation In Neurons and Cancermentioning
confidence: 99%